2013
DOI: 10.1016/j.neuron.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Robust Gamma Coherence between Macaque V1 and V2 by Dynamic Frequency Matching

Abstract: Current theories propose that coherence of oscillatory brain activity in the gamma band (30-80 Hz) constitutes an avenue for communication among remote neural populations. However, reports documenting stimulus dependency and time variability of gamma frequency suggest that distant neuronal populations may, at any one time, operate at different frequencies precluding synchronization. To test this idea, we recorded from macaque V1 and V2 simultaneously while presenting gratings of varying contrast. Although gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
300
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(341 citation statements)
references
References 53 publications
38
300
3
Order By: Relevance
“…The feedforward signature of γ is in line with recent studies showing stronger Granger causality for γ from V1 to V2 and from V1 to V4 than in the opposite direction (18,49,65). It is also reminiscent of a study in cats, showing that γ-oscillations propagate from the LGN to V1 with an average delay of ∼2 ms (47).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The feedforward signature of γ is in line with recent studies showing stronger Granger causality for γ from V1 to V2 and from V1 to V4 than in the opposite direction (18,49,65). It is also reminiscent of a study in cats, showing that γ-oscillations propagate from the LGN to V1 with an average delay of ∼2 ms (47).…”
Section: Discussionsupporting
confidence: 89%
“…At first sight, this result appears to contradict a recent finding that Granger causality between V1 and V2 in the α-range is strongest in the feedforward direction (18). We suspect that methodological differences (the previous study only selected electrode combinations with high γ-coherence) and perhaps differences between tasks are responsible for this discrepancy.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…While this mixture potentially limits comparability to invasive recordings, there are indications that visual areas synchronize their peak frequencies. In a recent study, Roberts et al (2013) showed, using simultaneous shaft electrode recordings in monkey regions V1 and V2, that gamma peak frequencies cofluctuate in these visual areas during visual stimulation with stimuli of different contrasts. V2 activity shows the same gamma peak frequencies as V1, and also V1-V2 coherence exhibits the same peak frequency as the individual areas.…”
Section: Exploring Putative Effects Of the Cortical Magnification Factormentioning
confidence: 99%
“…The peak frequency of visual gamma responses is modulated by properties of the visual stimulus such as size [Gieselmann and Thiele, 2008; Jia et al, 2013; Ray and Maunsell, 2011; van Pelt and Fries, 2013], contrast [Hadjipapas et al, 2015; Jia et al, 2013; Lowet et al, 2015; Perry et al, 2015; Ray and Maunsell, 2010; Roberts et al, 2013], motion [Friedman‐Hill, 2000; Muthukumaraswamy and Singh, 2013; Swettenham et al, 2009], motion velocity [Gray et al, 1990; Gray and Viana Di Prisco, 1997; Orekhova et al, 2015], eccentricity [van Pelt and Fries, 2013], noise masking [Jia et al, 2013], and cross‐orientation masking [Lima et al, 2010; Perry, 2015]. Across individuals, peak gamma frequency correlates with psychophysical performance in visual discrimination tasks [Dickinson et al, 2015; Edden et al, 2009].…”
Section: Introductionmentioning
confidence: 99%